2005
DOI: 10.1897/04-364r.1
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of the fungicide propiconazole and agricultural runoff sediments on the aquatic bryophyte Vesicularia dubyana

Abstract: Pesticides, firmly attached to the topsoil, might enter nearby watercourses at periods with high erosive loss of sediments. Therefore, exposure of aquatic organisms to these low mobility pesticides, in many cases, will coincide with a high sediment concentration. In this study, both individual and combined effects of propiconazole and runoff sediment on the aquatic model bryophyte Vesicularia dubyana are studied. Individual exposure to propiconazole induced responses in V. dubyana at rather low concentration l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Usage of these corrections results in 0.14-0.5 pH unit decrease of pK a values as compared to pK a values calculated from the non-corrected effective mobilities. For comparison, the values of the acid dissociation constants of the triazole fungicides and the 1,2,4-triazole itself calculated by SPARC online calculator [39] and pK a s found in the literature [8,14,40,41] are also listed in this Table. The pK a s determined by pCE in this work are slightly higher than the values calculated by SPARC online calculator [39]. The highest difference between the calculated and the experimentally determined pK a was observed for flusilazole, which contains silicon atom in its structure.…”
Section: Resultsmentioning
confidence: 99%
“…Usage of these corrections results in 0.14-0.5 pH unit decrease of pK a values as compared to pK a values calculated from the non-corrected effective mobilities. For comparison, the values of the acid dissociation constants of the triazole fungicides and the 1,2,4-triazole itself calculated by SPARC online calculator [39] and pK a s found in the literature [8,14,40,41] are also listed in this Table. The pK a s determined by pCE in this work are slightly higher than the values calculated by SPARC online calculator [39]. The highest difference between the calculated and the experimentally determined pK a was observed for flusilazole, which contains silicon atom in its structure.…”
Section: Resultsmentioning
confidence: 99%
“…Potter et al (2001) showed that the fungicide chlorothalonil presented a risk to aquatic life as a result of runoff from treated fields in southeastern states. Wu et al (2005) observed that propiconazole was toxic to aquatic bryophytes at low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…20000 Widenfalk et al [137] Mikroorganismen (Sediment) Bakterielle Aktivität 0,09 Johansson et al [135] Rana temporaria Larvalentwicklung 416000 Continued overleaf [139] Daphnia magna Entwicklung 250 Hurst & Sheahan [124] Saccharomyces cerevisiae Hefezell-Östrogentest 12500 (Routledge & Sumpter 1996) Wu et al [140] Vesicularia dubyana (Javamoos) Photosyntheserate 1 Bringolf et al [141] Lampsilis siliquoidea Glochidien-Tox. 19210 (48 h) Juvenil-Tox.…”
Section: Carassius Auratusmentioning
confidence: 99%